Titanium mesh and autogenous iliac bone graft: treatment of a mandibular fracture delayed for one year - (:unkn) unknown (My University, 1997)
In treatment of bone defects, transplantation of autogenous iliac bone and marrow give satisfactory results. Titanium mesh implants have also been used reconstruction of maxillofacial defects for years. Specifically, this technique of provides stabilization in ununited fractures of edentulous and atrophic mandibles, and facilitate bone grafting. This paper report the use of titanium mesh and autogenous iliac bone grafting in an ununited mandibular fracture one year after injury.
Keywords: Adult; Female; Humans; Chronic Disease; Follow-Up Studies; Titanium; Time Factors; Transplantation, Autologous; Surgical Mesh; Ilium; Mandibular Fractures